Single nucleotide polymorphisms of GEMIN3 modify the risk of primary Sjögren's syndrome in female patients - Wang, Dong; Zhang, Jingjing; Zhao, Yufei; Cao, Ruijie; Wang, Yingnan; Guo, Iren; Peng, Chenxing; Song, Yanrong; Zhang, Shasha (The American journal of the medical sciences, 2025)
MicroRNA (miRNA)-processing machinery may modify the risk of primary Sjögren's syndrome (pSS) by altering miRNA expression profiles. Inflammatory cytokines and reactive oxygen species (ROS) are also involved in pSS; however, the role of altered miRNAs expression in its pathogenesis is still unclear. We aimed to evaluate the relationship between single-nucleotide polymorphisms (SNPs) in miRNA processing machinery genes, including XPO5 (rs11077), RAN (rs14035), Dicer (rs3742330), TNRC6B (rs9623117), GEMIN3 (rs197412), and GEMIN4 (rs2740348), and the risk of pSS in female patients. The potential associations of cytokines and ROS with pSS-susceptible SNPs were also evaluated. The SNPs confirmed by polymerase chain reaction ligase detection reaction were genotyped in 74 female patients with pSS and 77 controls. The relationship was analyzed by Student's t-test, Wilcoxon rank-sum test, chi-square test, Pearson's correlation test, and binary logistic regression analysis. For rs197412 of the GEMIN3 gene, the genotype TT carrier was associated with a 2.172-fold increased risk for pSS when compared with that of CT+CC carrier (odds ratio: 2.172, 95% CI, 1.133-4.166, p=0.019). Simultaneously, the pSS-susceptible TT carriers were associated with increased interferon-γ (IFN-γ) (P < 0.001) and tumor necrosis factor-α (TNF-α) (P = 0.003) levels when compared with that of CT+CC genotype carriers in female patients with pSS. The subsequent analysis also showed a weak positive correlation between IFN-γ and TNF-α levels (r=0.271, P = 0.019). The predictors of GEMIN3 SNPs might modify pSS development in females by mediating the expression of miRNAs and therefore regulate the levels of IFN-γ and TNF-α.